Ontologias, categorias e interoperabilidade semântica - Moreira, Walter [UNESP]; Lara, Marilda Lopes Ginez (My University, 2012)
Explores the concept of interoperability as a means of cooperation, stressing the importance of promoting them from consistent information policies. Highlights the dependence of interoperability to the variations of language that account for sociocultural differences and associates its realization to common ontology construction as a means of enabling structures that can be integrated. Emphasizes the importance of using categories to provide the entire organization and to facilitate access by offering support the process of categorizing on concrete terminologies of specific domains and areas of activity, discourse communities references or of the speeches actually made.

Explora a noção de interoperabilidade como um instrumento de cooperação, salientando a importância de promovê-las a partir de políticas de informação consistentes. Ressalta a dependência da interoperabilidade às variações da linguagem que respondem pelas diferenças socioculturais e associa sua concretização à construção de ontologias comuns como meio de viabilizar estruturas que possam ser integradas. Enfatiza a importância do uso de categorias para prover organização ao conjunto e facilitar o acesso, propondo respaldar o processo de categorização nas terminologias concretas de domínios e áreas de atividade, referências das comunidades discursivas ou dos discursos efetivamente realizados.
Ontologies, categories and semantic interoperability